Mg/Ca Ratios in Synthetic Low-Magnesium Calcite: An Experimental Investigation - Jeremy M. Weremeichik; Rinat I. Gabitov; Aleksey Sadekov; Aleksandra Novak; Angel Jimenez; Rooban Venkatesh K. G. Thirumalai; Jac J. Varco; Andrew Dygert (Minerals, 2021)
The work presented sought to determine the effects of Mg/Ca ratios in solution have on Mg partitioning (KMg) between precipitated abiotic low-Mg calcite and solution. Experiments were set up so that Mg/Ca in precipitated abiotic calcite would match the Mg/Ca in planktonic foraminifera. This research intended to investigate the effect of Mg/Ca(Fluid) on KMg when the molar value of Mg/Ca(Fluid) was below 0.5, which is below the previously reported Mg/Ca range. The values of pH, salinity, and aqueous Mg/Ca were monitored during calcite precipitation, and Mg/Ca of calcite was determined at the end of experiments. Partition coefficients of Mg were evaluated as a ratio of Mg/Ca in calcite to the averaged ratio of aqueous Mg/Ca for each experiment.